Slave trading in the old South - Bancroft, Frederic, 1860-1945 (Southern classics series., 1996)
Through correspondence with people involved in the slave trade and interviews with former slaves, Bancroft exposed the commercial aspects of the American slave trade, including the breeding of slaves for future sale, the separation of slave families, the profitability of the trade, and the integration of slave traders into the highest ranks of southern society.